Bleeding of unknown cause and unclassified bleeding disorders; diagnosis, pathophysiology and management. Issue 6 (23rd October 2020) - Thomas, Will; Downes, Kate; Desborough, Michael J. R.
Abstract: Bleeding of unknown cause (BUC), also known as unclassified bleeding disorders (UBD), has been defined as a clear bleeding tendency in the presence of normal haemostatic tests. There are challenges in the diagnosis and management of these patients. BUC/UBD encompasses a heterogenous group of disorders which may include undiagnosed rare monogenic diseases, polygenic reasons for bleeding; and patients without a clear bleeding disorder but with a previous bleeding event. Nevertheless, these patients may have heavy menstrual bleeding or be at risk of bleeding when undergoing surgical procedures, or childbirth; optimizing haemostasis and establishing a mode of inheritance is important to minimize morbidity. The bleeding score has been used to clinically assess and describe these patients, but its value remains uncertain. In addition, accurate distinction between normal and pathological bleeding remains difficult. Several studies have investigated cohorts of these patients using research haemostasis tests, including thrombin generation and fibrinolytic assays, yet no clear characteristics have consistently emerged. Thus far, detailed genetic analysis of these patients has not been fruitful in unravelling the cause of bleeding. There is a need for standardization of diagnosis and management guidelines for these patients. This review gives an overview of this field with some suggestions for future research.